The Effect of Work Culture and Management Quality on Employee Performance: The Mediating Role of Work Commitment at Lampung Province Industry and Trade Department - Dewi Suma (Universitas Padjadjaran, 2024)
This study proposes to understand how work culture and quality management affect work commitment and its implications for employee performance in the context of civil servant workers at the Industry and Trade Department of Lampung Province. Random sampling method is carried out to choose 194 samples proportionally. The data is obtained by distributing questionnaires to the respondents, which are then analyzed using structural equation modeling (SEM) with AMOS version 22. The findings indicate that work culture positively and significantly influences work commitment, while work commitment positively and significantly influences civil servants’ performance. In addition, this study also confirms that work commitment has a greater influence in influencing civil servants’ performance at the Industry and Trade Department of Lampung Province. Work commitment mediates the effect of quality management on employee performance. To improve civil servants’ performance at the Industry and Trade Department of Lampung Province, the management should focus more on increasing employee work commitment through quality management. However, efforts to improve employee performance through other variables, such as work culture and quality management, must also be considered, although the impact is not significant. Suggestions for future researchers are to examine other mediating variables in improving employee performance.